Vitamin K and metabolic syndrome: is there a link? - Sara Beatriz Lameiras Tavares de Pinho (2020)
With approximately a quarter of the adult population in the world suffering from metabolic syndrome, finding strategies to delay, or even prevent, the development of diseases associated with this condition, such as cardiovascular diseases (CVD), type 2 diabetes (T2D) and obesity, is paramount. Metabolic syndrome is linked to malnutrition and micronutrients have been gaining acceptance as therapeutic tools for this condition. Low levels of the fat-soluble vitamins A, D and E seem to be associated with metabolic syndrome and, in recent years, it was discovered that vitamin K is more than just an antihaemorrhagic vitamin. It has anti-inflammatory and antioxidant properties and, in addition to its role in the synthesis of several Gla proteins, it seems to be involved in the regulation of metabolic pathways associated with metabolism. Vitamin K may protect from several diseases, including CVD, osteoporosis, obesity and T2D. Within this work, we present an overview of vitamin K sources, metabolism and biomarkers, as well as the current available evidence of the effect of vitamins K1 and K2 on inflammation, insulin resistance, obesity, dyslipidemia and high blood pressure, and their underlying mechanisms.